2020
DOI: 10.1038/s41587-020-0614-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolating live cell clones from barcoded populations using CRISPRa-inducible reporters

Abstract: We developed a functional lineage tracing tool termed CaTCH (CRISPRa Tracing of Clones in Heterogeneous cell populations). CaTCH combines precise clonal tracing of millions of cells with the ability to retrospectively isolate founding clones alive prior to and during selection, allowing functional experiments. Using CaTCH, we captured rare clones representing as little as 0.001% of a population and investigated the emergence of resistance to targeted melanoma therapy in vivo .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 48 publications
1
56
0
1
Order By: Relevance
“…Evolving CRISPR/Cas9 technology will also make it possible to genetically manipulate somatic cells in juvenile and adult inbred mice. Although tracking tumor heterogeneity and rare cell subpopulations is challenging, the novel methodology CaTCH (CRISPRa tracing of clones in heterogeneous cell populations) provides new opportunities to study clonal evolution in cancers (Umkehrer et al, 2020).…”
Section: Melanoma Challengesmentioning
confidence: 99%
“…Evolving CRISPR/Cas9 technology will also make it possible to genetically manipulate somatic cells in juvenile and adult inbred mice. Although tracking tumor heterogeneity and rare cell subpopulations is challenging, the novel methodology CaTCH (CRISPRa tracing of clones in heterogeneous cell populations) provides new opportunities to study clonal evolution in cancers (Umkehrer et al, 2020).…”
Section: Melanoma Challengesmentioning
confidence: 99%
“…This approach relies on the generation of insertion or deletion (indel) mutations by spCas9 nuclease in a target region to shift the translation frame of a reporter cassette, similar to vectors used to monitor gene-editing outcomes [8,19]. An alternative approach would be to use CRISPRa (dCas9-transcriptional activator) to activate marker expression in a barcode-dependent fashion [20][21][22][23]24]. However, we found that a lentiviral transcriptional activation-based reporter lacked specificity, in part due to a high background level of transcription in a fraction of cells subsequent to genomic integration of the reporter (Additional file 1: Fig.…”
Section: Design Of a Retrieval Vector Activated By Frameshift Mutationsmentioning
confidence: 99%
“…Simply, treatment naĂŻve melanoma cells were transduced with the transcriptional activator dCas9‐VPR and unique barcodes fused to an inducible fluorescent reporter tag. Following drug selection, enriched “drug resistant” clones were determined by genomic sequencing and barcode‐complementary sgRNAs were transduced back into a heterogeneous population of melanoma cells [132]. The fluorescent reporter is activated in the clone of interest, which can be isolated by fluorescence‐activated cell sorting and functionally characterized and compared to treatment naĂŻve founder cells.…”
Section: Identifying Novel Tumor Suppressive and Oncogenic Genes Usinmentioning
confidence: 99%
“…Even more sophisticated platforms have been developed recently, employing CRISPRi and CRISPRa, in addition to CRISPRko, and enabling combinatorial libraries (two sgRNAs per cell) to be assessed [130,131]. CRISPRa Tracing of Clones in Heterogeneous cell populations, or CaTCH, is another new platform that builds on lineage tracing that permits functional characterisation and comparison of founder clones with their post-selection counterparts [132]. CaTCH was utilized to discern whether melanoma cells had pre-existing resistance mechanisms to RAF and MEK inhibitors, or whether they acquired resistance during treatment in vivo [132].…”
Section: Insights Into Future Directions Of Crispr Approaches In Immumentioning
confidence: 99%
See 1 more Smart Citation